1974
DOI: 10.1530/jrf.0.0400105
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Variation in the Seasonal Onset of Oestrus and Litter Size in the Ewe

Abstract: The relationship between the date of first oestrus of the breeding season and litter size when mating took place at the first, second, third, fourth or fifth oestrus was studied in 160 Polled Dorset Horn ewes which conceived to their planned mating. The ewes were maintained in one flock with vasectomized`teaser' rams at a ratio of less than thirty ewes to one ram. Checks were made twice daily for ewes in oestrus. At first oestrus, ewes were allocated to be mated at their first, second, third, fourth or fifth o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

1976
1976
1997
1997

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 6 publications
1
7
0
Order By: Relevance
“…(1974) that fertility is higher at third oestrus than at puberty. Furthermore, they agree with earlier reports of an increase in fertility during the early part of the breeding season in ewe lambs (Hare and Bryant, 1985) and ewes (Lees, 1978;Hendy and Bowman, 1978). In addition, these results extend earlier observations by demonstrating that mating ewe lambs at third oestrus rather than puberty, will significantly improve lambing performance.…”
Section: Discussionsupporting
confidence: 92%
“…(1974) that fertility is higher at third oestrus than at puberty. Furthermore, they agree with earlier reports of an increase in fertility during the early part of the breeding season in ewe lambs (Hare and Bryant, 1985) and ewes (Lees, 1978;Hendy and Bowman, 1978). In addition, these results extend earlier observations by demonstrating that mating ewe lambs at third oestrus rather than puberty, will significantly improve lambing performance.…”
Section: Discussionsupporting
confidence: 92%
“…Hendy and Bowman (1974) suggested that good body condition is associated with earliness of breeding but this proposition was not supported by Ducker and Boyd (1974) who could demonstrate no difference in the mean date of first oestrus for Greyface ewes differing in live weight by 14-3 kg. Hendy and Bowman (1974) suggested that good body condition is associated with earliness of breeding but this proposition was not supported by Ducker and Boyd (1974) who could demonstrate no difference in the mean date of first oestrus for Greyface ewes differing in live weight by 14-3 kg.…”
Section: Discussionmentioning
confidence: 97%
“…In a prolific genotype, Hendy and Bowman (1974) associated early oestrus onset with high litter size and demonstrated a progressive increase in litter size from the first to the third oestrous cycle of the breeding season. These data suggest that ovulation rate increases over this time but no such increase could be demonstrated by Sweeney and O'Callaghan (1996) who measured ovulation rate during each of the first five cycles of the breeding season in crossbred ewes.…”
Section: Discussionmentioning
confidence: 99%
“…It would therefore appear that the artificial photoperiod was effective in eliminating the natural seasonal variation (Hendy & Bowman, 1974) in ovulation rate.…”
Section: Discussionmentioning
confidence: 99%